2005
DOI: 10.1115/1.2181601
|View full text |Cite
|
Sign up to set email alerts
|

Power Loss Predictions in Geared Transmissions Using Thermal Networks-Applications to a Six-Speed Manual Gearbox

Abstract: A model is presented which makes it possible to predict power losses in a six-speed manual gearbox. The following sources of dissipation, i.e., power inputs in the model, are considered: (i) tooth friction; (ii) rolling element bearings; (iii) oil shearing in the synchronizers and at the shaft-free pinion interfaces; and (iv) oil churning. Based upon the first principle of Thermodynamics for transient conditions, the entire gearbox is divided into lumped elements with a uniform temperature connected by thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
131
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(132 citation statements)
references
References 5 publications
0
131
0
1
Order By: Relevance
“…Drag torque models include resistance torques from bearings, gears, in the form of windage and friction, [19,20] in the concentrically aligned primary shafts, and in the wet clutch pack [16]. For the DCT in particular resistances as split into groups associated with the absolute speed of the target gear, from gears and bearings, and those linked to the relative speed in the clutches, notably shaft, bearing, and clutch viscous losses.…”
Section: Modelling the Synchronisermentioning
confidence: 99%
See 1 more Smart Citation
“…Drag torque models include resistance torques from bearings, gears, in the form of windage and friction, [19,20] in the concentrically aligned primary shafts, and in the wet clutch pack [16]. For the DCT in particular resistances as split into groups associated with the absolute speed of the target gear, from gears and bearings, and those linked to the relative speed in the clutches, notably shaft, bearing, and clutch viscous losses.…”
Section: Modelling the Synchronisermentioning
confidence: 99%
“…Further drag torque modelling during the synchronisation process indicates peak drag is realised at speed synchronisation between shaft and gear as a result of high viscous drag in the wet clutch and peak clutch slip speed being achieved at this time [18]. [16,19,20] all have investigated drag torque to some extent, it is generally understood that whilst it is possible to identify and model drag torque, the high level of uncertainty and variability associated with drag torque limits the capacity to influence drag through good transmission design. This paper will therefore evaluate several techniques for active control of chamfer alignment in synchroniser mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly [6] demonstrated the impact of temperature dependent variation of operating fluid properties on the accuracy of results, providing improvements of up to 10% when temperature dependent and independent models are compared. In both papers [6,12] consideration of bearing losses, gear windage and churning, and tooth friction are of primary consideration as sources of drag. These sources are responsible for the development of drag losses in the general operating of transmission systems and gear pairs.…”
mentioning
confidence: 95%
“…Numerical analysis of drag torque on transmissions has been performed by Changenet et al [6] (helical gears) and Anderson and Loewenthal [2] (spur gears), and on gear pairs by Heingartner and Mba [12], with the inclusion of successful experimental validation. Significantly [6] demonstrated the impact of temperature dependent variation of operating fluid properties on the accuracy of results, providing improvements of up to 10% when temperature dependent and independent models are compared.…”
mentioning
confidence: 99%
“…Although lubricant churning can be considered as a major source of power loss in gearboxes, splash lubrication also contributes to the regulation of gear bulk temperature since some heat is removed from the tooth faces by centrifugal fling-off as demonstrated by Blok [11]. Using a general thermal model of an automotive manual gearbox, Changenet et al [12] have confirmed the influence of the heat exchanges between the oil sump and several rotating elements on the global thermal behaviour and emphasized, in particular, the role of the immersion depth. Höhn et al [13] have conducted a number of experiments showing that lowering the oil level in the sump reduces churning losses but also leads to higher gear bulk temperatures.…”
Section: Introductionmentioning
confidence: 99%